Valorization Of Sargassum Seaweed For Sustainable Agriculture Based On Compost And Biochar Production And Application In Okra (Abelmoschus Esculentus (L.) Moench) Cultivation In Coastal Ghana - Klogo Phanuel Yao (University of Cape Coast, 2024)
The annual beaching of large volumes of Sargassum spp. along Ghana's coastline presents both challenges and opportunities for local communities. This study, from 2021-2023, investigated the potential of utilizing Sargassum for agricultural purposes, focusing on its conversion to compost and co-composted biochar, with particular emphasis on okra production, a crucial livelihood activity for many coastal residents in Ghana. A survey involving 782 fishermen from major fishing districts in the Western, Central, and Volta regions revealed extensive local knowledge about Sargassum's beaching patterns, physical characteristics and associated socio-economic impacts, including reduced fish catches, income loss, damage to fishing equipment, and health concerns. A parallel survey of 1,021 farmers indicated widespread use of organic manures in crop cultivation, with okra as the most popular vegetable crop. Farmers expressed willingness to adopt and purchase Sargassum-based compost, recognizing its potential benefits. IBM- SPSS was used to analyse data. Four compost formulations with varying proportions of Sargassum were developed and analysed. Significant differences (P = 0.01) in pH, electrical conductivity (EC), ammonium-nitrogen (NH4+-N), nitrate-nitrogen (NO3--N), total carbon, and nitrogen were detected throughout the mesophilic, thermophilic, and cooling phases of the composting process, in addition to the mature compost. The pH of the composts ranged from 6.5 to 7.9, while available P content varied between 992.0 mg/kg and 1,764.0 mg/kg. ANOVA was done using GenStat. Incubation experiments assessed the mineralization dynamics of NPK in the different Sargassum composts. Results showed significant variations (P = 0.01) in pH (7.0-7.5), EC (24.7-149.2 μS cm-1), NO3--N (0.29-5.58 μg g-1), P (0.90-11.00 μg g-1), and K (0.38-0.44 cmol kg-1). ANOVA was done using GenStat. Experiments conducted in pots with the application of Sargassum compost indicated significant (P=0.01) improvements in growth and yield of okra. ANOVA was done using GenStat. Analysis of variance using GenStat of soil after harvest showed significant increases in pH, electrical conductivity (EC), organic carbon, total nitrogen, available phosphorus, exchangeable acidity (Al3+ + H+), and effective cation exchange capacity (ECEC). A strong positive correlation was observed between pH and all tested parameters, with pH values ranging from 6.2 to 7.9. Compost-amended soils consistently outperformed those treated with inorganic fertilizers across all measured parameters. This study demonstrated the feasibility and benefits of repurposing Sargassum seaweed into high-quality compost for agricultural use in coastal Ghana. The study examined the environmental issues associated with the accumulation of Sargassum and proposed a sustainable approach to soil fertility improvement and increase in crop yields, with a specific focus on okra farming. The positive reception from local farmers and the superior performance of Sargassum-based composts compared to inorganic fertilizers suggest a promising pathway for sustainable agricultural practices in coastal communities. These findings have significant implications for waste management, coastal livelihoods, and food security, potentially serving as a model for other regions facing similar Sargassum influxes.
xxxi,359p:,ill
Keywords: Compost mineralisation Cooling phase Mesophilic phase Okra Sargassum compost Thermophilic phase